Multimode resistance training to improve baseball batting power - Ebben, W. P.; Fotsch, Hartz, K. K. (Strength and Conditioning Journal, 2006)
This article reviews a variety of resistance training modes that can be used to increase baseball batting power. These modes include strategies that are biomechanically and velocity specific to batting.